(untitled) (Journal of Student Affairs in Africa, 2022)
​ Abstract Peer pressure and alcohol use in tertiary institutions seems to remain a challenge amongst emerging adults. The study examined the moderating influence of gender on the association between dimensional peer pressure and alcohol consumption. A non-probability convenient sampling technique was employed. The sample consisted of 414 participants who were students recruited from 6 faculties. Data was collected using Peer Pressure Inventory (PPI) and Alcohol Use Dependence Identification Test (AUDIT) in an online platform. Data was analysed using the Statistical Package for the Social Sciences Version 25 (SPSS-25). Structural equation modelling was used to test assumptions. The was no gender difference in terms of the relationship between peer conformity and misconduct on alcohol use. Results indicated an increased family involvement whichpredicted lower alcohol consumption among females but not in males. School and peer involvements were not related to alcohol use in both gender. Family involvement against peer influence on the use of alcohol, may be a protective factor in females but not in males. Males were more likely to conform to peer pressure than females. Key words: Peer pressure; Family involvement; Alcohol use; Gender; Moderation